A dialética rural-urbano em visualidades de mulheres caipiras, em "Chocolate com Pimenta", "Alma Gêmea" e "Êta mundo bom!" - Olívia Érika Alves Resende (2019)
We regard the study of visualities – concept taken from W. J. T. Mitchell (2009) and used here along with the idea of televisuality (ROCHA, 2018) – as the most productive means of accessing cultural matrices, concept-metaphor proposed by Martín-Barbero (2009) and understood as referring the historical and local determinacies that sustain regimes of seeing and showing shared in a certain sociocultural context and perceived on televisual products. Our main objective is to investigate caipira women’s visualities in Brazilian telenovelas broadcasted by Rede Globo de Televisão: Chocolate com Pimenta’s Márcia (played by Drica Moraes); Alma Gêmea’s Mirna (Fernanda Souza); and Êta Mundo Bom!’s Mafalda (Camila Queiroz). We aim to find what the image/text composite that constitutes pictures (MITCHELL, 2017) of these characters shows about cultural matrices and regimes of seeing and showing that sustain caipira women’s visualities. We also aim to notice the ways these pictures talk with their audiences, that is, the experiences the pictures may offer to viewers. This research, besides of taking into account the historical and cultural relevance of the images in Latin America’s popular cultures – as this aspect is indicated by Serge Gruzinski (2006) and Jesús Martín-Barbero (2009) –, is associated to the interdisciplinary field of visual culture studies and tries to adopt what Mitchell (2009, 2017) points to as “giving image to theory”. This investigative path enquiries pictures presented by hybrid media, as is the case of television. Instead of using previous concepts of caipira woman and testing their validity in regard to the mentioned telenovelas, we inquire verbo-visual components of the televisual representations, in order to perceive different images that may be generated by the same materiality and how these may interact with visuality regimes integrated to the culture in which those representations take part. This work articulates visual studies method with television style, as the last is proposed by Jeremy Butler (2010); we regard the particularities of a complex, multifarious medium as television, whose unique creative form and creative regimes are shaped in conjunction with culture (MITTELL, 2010; MARTÍN-BARBERO, 2009). By investing in the analysis of the image/text dialectic composite displayed by the characters’ pictures, this work shows different ways the rural and the urban take part in the three caipira women’ visualities, whose bodies are localized and, at the same time, connected to utopias linked to certain cultural matrices. Between the rural and the urban, the elevated and the mundane, the archaic and the modern, the comedy and the drama, the human and the nonhuman, the artistic and the useful, the telenovelas show how Márcia, Mirna and Mafalda share cultural and gender dramatic issues experienced by complex caipiras, mestiças who live between the rural and the urban. Simultaneously, those women contribute to the construction of narratives of nation that are based on the recreation of past situations.